Samorząd terytorialny szczebla powiatowo-gminnego w II Rzeczypospolitej wobec funkcjonowania oświaty i szkół powszechnych na wsi (1918-1939) - Turkowski, Romuald (Zeszyty Wiejskie, 2018)
The paper describes the role of local authorities of poviat and commune level in the Second Republic of Poland in the area of widely understood support for the functioning of education system in common schools in rural areas in the period between 1918-1939. The paper outlines the main rules of the functioning of local authorities, paying attention to its democracy between 1918-1926 and its drastic distortions and restrictions introduced by the political camp of Marshal Józef Pilsudski, particularly between 1933-1939 when the reform of local authorities was introduced in a way that it could be beneficial for this political camp. The subsequent part of the article presents, among others, forms of cultivating the memory about the teachers who fought for the Polish education under foreign occupation.